Struvite as an Alternative Fertilizer Component in Soilless Cultivation of Marigold (Tagetes erecta L.) - Neofytou, Giannis; Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2026)
Nutrient recovery from wastewater presents a promising method of enhancing the sustainability of agricultural production and reducing environmental pollution. Struvite, a byproduct of wastewater treatment represents a sustainable source of nutrients for use in agriculture. In this context, this research examines struvite as a potential fertilization component of container-grown marigold (Tagetes erecta L.), a phosphorus-sensitive model plant. The study used decreased (0.5×), standard (1×), and increased (2×) rates of conventional (CON1, CON2, CON3) and struvite-modified (STR1, STR2, STR3) fertilization, with or without synthetic fertigation. Struvite addition in peat maintained the pH within optimal ranges for horticultural substrates. However, electrical conductivity increased (up to 83.8%) with the increasing fertilization levels. Struvite treatments maintained equivalent growth, marketability and flower production compared to conventional fertilization. Fertilization rates, however, did not exert significant influences. Leaf chlorophyll content was also unaffected, although differences were found among fertilization rates. Any differences in growth or physiology were suppressed by supplementary fertigation. Increasing fertilization rates enhanced the accumulation of nutrients in leaves and flowers. However, conventional fertilization caused increased nitrogen (up to 84.3%) and sodium (up to 87.6%) accumulation. Total phenolic content in leaves and flowers was maintained with struvite. In contrast, its addition caused elevated leaf antioxidant activity and flower carotenoids, contingent on fertilization rates. Plants treated with STR2 were undergoing adaptive responses to combat stress, having increased malondialdehyde (MDA) content (60.6%) compared to CON2. Conversely, prior activation of the antioxidant mechanisms was evident in plants treated with STR3, as despite the elevated hydrogen peroxide levels, MDA was reduced by 23.6% compared to use of STR2. These results indicate that, even in decreased fertilization, the growth and flower production of marigold could be maintained with struvite. Finally, optimizing struvite fertilization rates may contribute to enhanced quality and nutritional value of edible marigold flowers, while supporting sustainable fertilization and resource recovery practices.
Keywords: Alternative fertilization; Edible flowers; Nutrient recovery; Struvite